2017
DOI: 10.15761/ohc.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Profile of oral health students over a ten year period and their practice intentions after graduation

Abstract: Objective: Limited research has been published on oral health therapists, particularly Australian cohorts of Bachelor of Oral Health (BOH) students who will graduate as oral health therapists. Aside from selection criteria and sample characteristics of students from some institutions, little is known about factors influencing career choice and career aspirations and workplace intentions after graduation. This study describes the characteristics, career choice factors and career aspirations of first year studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Approximately 90% of respondent oral health students in this study were female and in their mid‐twenties. This is consistent with demographic profiles of previous BOH student studies which reported between 61 and 97% were female and were on average between 20 and 24 years of age 15,19,22 . However, the response rate and cross‐sectional study design can limit generalisability.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Approximately 90% of respondent oral health students in this study were female and in their mid‐twenties. This is consistent with demographic profiles of previous BOH student studies which reported between 61 and 97% were female and were on average between 20 and 24 years of age 15,19,22 . However, the response rate and cross‐sectional study design can limit generalisability.…”
Section: Discussionsupporting
confidence: 89%
“…Approximately half of all students in this study reported that their primary intention after study was to work in a clinical career in the private sector, and this is similar to recent BOH literature 19 . In Australia and New Zealand, the dental health system is a mixed‐modelled system where OHPs can practice in private fee‐for‐service clinics, or in public sector clinics where treatments are subsidised or fully funded by the government.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…10,11 Furthermore, it was not uncommon for practising and student DHs and OHTs to pursue a career in dentistry. [12][13][14][15] Studies found that some OHT students ranked dentistry as their primary career choice and hoped to use OHT as a stepping-stone for entry into dentistry. [13][14][15] The current literature on OHT careers has mainly utilized quantitative studies to examine the factors associated with career satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Studies found that some OHT students ranked dentistry as their primary career choice and hoped to use OHT as a stepping-stone for entry into dentistry. [13][14][15] The current literature on OHT careers has mainly utilized quantitative studies to examine the factors associated with career satisfaction. Therefore, well-designed qualitative research is needed to critically examine the enablers and barriers to OHTs having a satisfying career.…”
Section: Introductionmentioning
confidence: 99%